Digital module development of islamic education to improve student independence in learning at middle school program - Ahmad Bukhori; Hamsu Abdul Gani; Muhammad Yahya (Goodwood Publishing, 2025)
Purpose: This study aimed to identify the need, design, validity, practicality, and effectiveness of developing digital modules for Islamic Religious Education to enhance students’ learning independence. Research methodology: This study examines a type of research and development (R&D) and develops a digital module for Islamic Education using the ADDIE model (analysis, design, development, implementation, evaluation). A learning independence questionnaire was administered to 70 students at Insan Cendekia Madani Middle School, Serpong, to assess the effectiveness of the module delivered via an online platform. Results: The results indicate the need for a digital Islamic Religious Education module to enhance students' learning independence. The design produced a module, supporting tools, and research instruments. Validation tests confirmed the validity of the module based on expert evaluations. Conclusion: The developed digital Islamic Religious Education module is a valid and potentially effective tool for promoting student learning independence. The structured design and integration with online platforms support interactive, flexible, and self-paced learning, which aligns with current educational demands.Limitation: This research was limited to a single school context with a relatively small sample size of 70 students, which may affect the generalizability of the findings to other regions or educational settings. Furthermore, this study primarily measured short-term learning independence without assessing its long-term impact.Contribution: This study contributes to the growing body of literature on digital learning in Islamic Religious Education by offering a validated and practical module design based on the ADDIE model. It provides a replicable framework for educators and policymakers seeking to enhance independent learning through technology-assisted instruction in similar educational contexts in the future.